2007
DOI: 10.1089/hum.2007.090
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing DNA Vaccine Potency by Combining a Strategy to Prolong Dendritic Cell Life and Intracellular Targeting Strategies with a Strategy to Boost CD4+ T Cells

Abstract: Intradermal administration of DNA vaccines, using a gene gun, represents an effective means of delivering DNA directly into professional antigen-presenting cells (APCs) in the skin and thus allows the application of strategies to modify the properties of APCs to enhance DNA vaccine potency. In the current study, we hypothesized that the potency of human papillomavirus (HPV) type 16 E7 DNA vaccines employing intracellular targeting strategies combined with a strategy to prolong the life of dendritic cells (DCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 18 publications
(15 reference statements)
0
21
0
Order By: Relevance
“…Doxorubicin combining vaccination using a gene gun or i.p. injection DNA-coated gold particles were prepared according to a previously described protocol [16] and were delivered to the shaved abdominal region of mice with helium-driven gene gun (Bio-Rad, Hercules, CA, USA) with a discharge pressure of 400 lb/in 2 . Either doxorubicin (5 mg/kg) or 0.9% NaCl normal saline (control) was injected into mice via the tail vein or intraperitoneal cavity 1 week prior to DNA vaccination.…”
Section: Plasmid Dna Constructs and Dna Preparationmentioning
confidence: 99%
“…Doxorubicin combining vaccination using a gene gun or i.p. injection DNA-coated gold particles were prepared according to a previously described protocol [16] and were delivered to the shaved abdominal region of mice with helium-driven gene gun (Bio-Rad, Hercules, CA, USA) with a discharge pressure of 400 lb/in 2 . Either doxorubicin (5 mg/kg) or 0.9% NaCl normal saline (control) was injected into mice via the tail vein or intraperitoneal cavity 1 week prior to DNA vaccination.…”
Section: Plasmid Dna Constructs and Dna Preparationmentioning
confidence: 99%
“…One way to improve the efficiency of DNA vaccination could be co-administration of DNA encoding antigen with DNA encoding inhibitors of apoptosis such as Bcl-X L protein [6,7,10,11]. Kim and colleagues have demonstrated that co-administration of plasmids encoding E7 of papilloma virus and Bcl-X L enhanced antigen-specific CD8+ T cell-mediated immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…One potential strategy to further enhance DNA vaccine potency is to prolong Dendritic cell (DC) survival by co-administrating DNA vaccine encoding antigen with DNA encoding inhibitors of apoptosis to DCs [6,7]. The anti-apoptotic molecules are hypothesized to prolong the lifespan of these critically important DCs thus allowing longer expression and presentation of the antigen with which they were co-transfected [6,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, we have shown that immunization with DNA vaccines encoding Ii-PADRE DNA leads to the generation of high numbers of PADRE-specific CD4 ϩ T cell immune responses in mice (12). Furthermore, coadministration of E7 DNA vaccines with Ii-PADRE DNA has led to enhanced E7-specific CD8 ϩ T cell immune responses and antitumor effects in vaccinated mice (12,13). Therefore, DNA vaccination encoding Ag of interest with Ii-PADRE DNA serves as a potentially useful means to improve DNA vaccine potency through the induction of CD4 ϩ T cells.…”
Section: ) Thus Strategies To Induce Cd4mentioning
confidence: 99%